(untitled) (Research, Society and Development, 2023)
Sex in general becomes as common to women as it is more common to women who observe psychiatric eating habits, because behaviors that are strange to psychiatric diets are common. body image distortion. The aim of this study was to analyze the relationship between body image and status, and to assess resistance to nutritional restriction, in students. This is a cross-sectional, descriptive study with an approach approach. The research was carried out between the months of September and 2019, with female students, aged between 18 and 59 years of November, who were regularly enrolled in a private higher education institution in the city of Campina Grande-PB. Data were identified through patient identification, with different social, social, demographic and life information, demographics and patient identification; Image Self-Perception Questionnaire; Binge Eating Scale (ECAP) and Patient Health Questionnaire-9 (PHQ-9). In addition, a nutritional assessment was performed, for the Body Mass Index, BMI and Waist Circumference (WC). From the results of the present research, it is concluded that even considered high in its entirety, the studied group had its body image compatible with reality, presenting it refers to the extension index of the current body image. Finally, this study draws attention to the proportion of young students who are unhappy with their body image.